Examining the Impact of Study Habits and Learning Styles on Academic Performance in Islamic Religious Studies - Sri Rezeki Harahap; Siti Halimah; Akmal Walad Ahkas (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aimed to determine: 1) The contribution of study habits to the learning outcomes of Islamic religious education students. 2) The contribution of learning styles to the learning outcomes of Islamic religious education students, and 3) The contribution of learning habits and learning styles to the learning outcomes of Islamic religious education students. This type of research is quantitative, with the research design used ex post facto. The data collection tool uses a research instrument in the form of a questionnaire to obtain information about study habits and student learning styles, and documentation is used to obtain information about student learning outcomes, with a sample size of 73 students from a total population of 330. The study concluded that 1) Study habits contributed to 43.5% of students' learning outcomes in Islamic religious education. 2) Learning style contributes to the Islamic religious education learning outcomes of students of 18.1. These findings indicate that learning style is one of the determining pillars for increasing student Islamic religious education learning outcomes, and 3) study habits and learning styles together contribute to learning outcomes by 61.4%. In comparison, the remaining 38.6% comes from outside the variables of this study. The findings recommend that academic performance can be improved through study habits and learning styles.